Avaliação transversal dos níveis de ferritina sérica no segundo e terceiro trimestres gestacionais em portadoras de pré-eclâmpsia e diabetes mellitus gestacional - Aluana Rezende Parola (2013)
The iron as a potent pro-oxidant is responsible for the induction of oxidative stress, with consequent endothelial injury, one of the patients in the pathophysiology of preeclampsia. The accumulation of iron in pancreatic beta-cells may also be responsible for the damage these cells can produce insulin resistance and consequently gestational diabetes. This study aims to identify, in the second and third trimesters, the average concentration of ferritin in a group of healthy pregnant women, compared to two groups of pregnant women with gestational diabetes and preeclampsia. It is cross-sectional design, so that was collected in isolation ferritin into three groups: women with preeclampsia, women with gestational diabetes and control group. First,the mean and standard deviations of ferritins were performed by analysis of variance (ANOVA) and comparison between groups was performed by Student's t test and after that, nonparametric test was applied . The results revealed mean ferritin in the control group of 22 ng / mL in the group of patients with gestational diabetes to 27ng/mL and the group of women with preeclampsia than 33 ng / mL. In the comparison between the groups showed that the p value was not statistically significant in groups. It was concluded that this study design was not able to demonstrate the significance of the value of ferritin alone. For this, it is suggested that further studies with different methodologies and with the same purpose.